L’archive comme enjeu de présentation de soi : la mémoire du syndicat des ouvriers des savonneries à Naplouse, Cisjordanie - Véronique Bontemps (Ateliers d'Anthropologie)
This article is based on the “quest for archives” I pursued in the context of a study on the soap factory workers’ union in Nablus. It begins by considering the elusive character of this union, which left few material traces of its existence. Next I examine how written documents were used by two former soap factory workers to construct the memory of the union. I show that these workers used two parallel systems to legitimise their words—systems that, far from clashing, reinforced each other: the possession of “authentic documents” should not so much make the discourse they contain more believable, but rather lend authority to their words. The article ultimately considers the power of discourse, particularly in an interview context.